Isolation of multidrug-resistant acinetobacter calcoaceticus strains from rhizosphere of tomato (Bangladesh Journal of Botany, 2025)
Acinetobacter species have significant challenges as pathogens because of their resistance to various antibiotics. Most studies have focused on clinically significant multidrug-resistant A. baumannii strains. This is the first report on multidrug-resistant A. calcoaceticus strains from soil in Bangladesh. A total of four tetracycline-resistant A. calcoaceticus strains were isolated from the rhizosphere soil of a tomato field. To profile their multidrug resistance patterns, the strains were examined by the Kirby-Bauer disk diffusion method using ten antibiotics from seven different classes. Multidrug-resistant strains were identified by 16S rRNA gene analysis and these strains were found to be highly resistant to ampicillin, erythromycin, and colistin. Among the four strains, the tetracycline-resistant BOTRUEML127 demonstrated the most significant resistance profile against eight antibiotics belong to five different classes. Multidrug-resistant A. calcoaceticus indicates a risk of severe infection if the soil isolates are disseminated into the hospital environment.Bangladesh J. Bot. 54(4): 943-948, 2025 (December)